One-step preparation of novel 1-(N-indolyl)-1, 3-butadienes by base-catalysed isomerization of alkynes as an access to 5-(N-indolyl)-naphthoquinones. Issue 63 (23rd October 2018) - Pis Diez, C. M.; Fernandez, J. F.; Di Venosa, G.; Casas, A.; Pis Diez, R.; Palermo, J. A.
Abstract : A series of novel 1-( N -indolyl)-1, 3-butadienes, was easily prepared in one step and used for the synthesis of 5-( N -indolyl) naphthoquinones. Abstract : A series of novel 1-( N -indolyl)-1, 3-butadienes, as (1 : 1) mixtures of the ( E ) and ( Z ) dienes, was prepared in one step by base-catalysed isomerization of N -alkylindoles with a terminal butyne chain. The reaction conditions are mild, and in all cases the yields were very high (>90%). The ( E ) and ( Z ) dienes were separable by preparative TLC and could be fully characterized. This isomerization proceeded readily in the case of a butynyl chain, but didn't take place with a pentynyl chain. A mechanism was proposed for this reaction, based on previous studies on the isomerization of alkynes in basic media, and a key intermediate that supports the proposed mechanism could be isolated and fully characterized. A theoretical study of the proposed mechanism was performed by computational methods and the results validated the proposal. The reactivity of the synthesized dienes was studied in Diels–Alder reactions with p -benzoquinone, to obtain a small library of new 5-( N -indolyl)-1, 4-naphthoquinones.The lack of reactivity in the case of the ( Z ) isomers was explained by calculation of the rotational curves of the central bond of the ( Z ) and ( E ) dienes. Finally, the cytotoxicity of the new 5-( N -indolyl)-1, 4-naphthoquinones was tested against a panel of three cell lines.